2013
DOI: 10.1111/1365-2435.12057
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of constitutive immunity: maternal vs. endogenous influences

Abstract: Summary1. Variation in ontogeny and strength of immune defence mechanisms can be integrally related to variation in life-history strategies and determined by trade-offs during development. However, little is known about the ontogeny of immune function in wild birds, especially in altricial birds and in a comparative context across altricial species with diverse life-history strategies. 2. In this study, we examined the ontogeny of constitutive immunity in a group of 22 passerine species sampled in tropical Ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 52 publications
0
24
0
Order By: Relevance
“…Life-history theory posits that, within and among species, investment in immune function should vary with pace of life (Ricklefs and Wikelski 2002, Lee 2006). Specifically, investment in general and inflammatory immune responses should be favored in short-lived species with rapid growth, short generation times, and high juvenile mortality (i.e., type III survivorship), whereas specific and humoral immune responses should be favored in long-lived species with longer development times and type I survivorship (Mauck et al 2005, Tieleman et al 2005, Martin et al 2007, Lee et al 2008, Arriero et al 2013). PHA-induced skin swelling is a very general measure of cutaneous immune responsiveness that encompasses components of both innate and acquired immunity (Martin et al 2006b), although recent work suggests that this response is primarily innate and that the adaptive component contributes much less to this response than traditionally thought (Vinkler et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Life-history theory posits that, within and among species, investment in immune function should vary with pace of life (Ricklefs and Wikelski 2002, Lee 2006). Specifically, investment in general and inflammatory immune responses should be favored in short-lived species with rapid growth, short generation times, and high juvenile mortality (i.e., type III survivorship), whereas specific and humoral immune responses should be favored in long-lived species with longer development times and type I survivorship (Mauck et al 2005, Tieleman et al 2005, Martin et al 2007, Lee et al 2008, Arriero et al 2013). PHA-induced skin swelling is a very general measure of cutaneous immune responsiveness that encompasses components of both innate and acquired immunity (Martin et al 2006b), although recent work suggests that this response is primarily innate and that the adaptive component contributes much less to this response than traditionally thought (Vinkler et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A few studies focusing on the constitutive immunity of short-lived passerine species found evidence of a potential trade-off between the development of immunity and growth rate (Soler et al 2003;Brommer 2004;Mauck et al 2005). Ultimately, increased maternal (exogenous) contributions could be observed as part of compensating mechanisms (Arriero et al 2013). We did not find any evidence of an association between the dynamics of decay of the maternal antibodies throughout the chickrearing period and the individual growth rate of nestlings.…”
Section: Transgenerational Immunization Of Slow-growing Offspringmentioning
confidence: 99%
“…However, fast growth can also negatively affect a broad array of traits related to organismal quality (Arendt ; Alonso‐Alvarez et al . ; Arriero, Majewska & Martin ) and can reduce longevity (Metcalfe & Monaghan ; Hulbert et al . ; Lee, Monaghan & Metcalfe ; but see Martin et al .…”
Section: Introductionmentioning
confidence: 99%